Cyclic deformation and microstructure evolution of high Nb containing TiAl alloy during high temperature low cycle fatigue. (June 2017) - Ding, Jie; Liang, Yongfeng; Xu, Xiangjun; Yu, Huichen; Dong, Chengli; Lin, Junpin
Highlights: Disparity in cyclic deformation behavior due to strain amplitude was investigated. TEM observations and EBSD techniques revealed the phase transformations. B2 phase transformation and γ recrystallization are detrimental to fatigue life. Twin boundaries can promote discontinuous dynamic recrystallization process. The fracture mode is a combination of ductile fracture and intergranular fracture. Abstract: The cyclic stress-strain (CSS) behavior of high Nb containing TiAl alloy with a duplex microstructure was investigated at 850 °C. Transmission electron microscope (TEM) observations and electron backscattered diffraction (EBSD) techniques were carried out to obtain insight into the microstructure evolution governing this behavior. At low strain amplitude, the material exhibits a rapid saturation of stress amplitude. At intermediate and high strain amplitude, the CSS behavior is characterized by generally cyclic softening. The changes of microstructure are strain-induced phase transformations and dynamic recrystallization, which lead to a degradation of lamellar microstructure. Twin boundaries can promote discontinuous dynamic recrystallization of γ phase, for processing relatively high energy. α2  + γ → B2, α2  → B2, and α2lamellae  → γ phase transformations are detrimental to fatigue life of the material, because fracture propagation are usually along B2 phase boundaries and γ grain boundaries, thus, the fracture mode is a combination of ductile fracture and intergranular cleavage fracture.